Chemical inhibition of ER aminopeptidase 1 as a tool for regulating the immunopeptidome of cancer cells. (October 2022) - Koumantou, Despoina; Barnea, Eilon; Martin-Esteban, Adrian; Maben, Zachary; Papakyriakou, Athanasios; Kokkala, Paraskevi; Pratsinis, Harris; Georgiadis, Dimitris; Stern, Lawrence J.; Admon, Arie; Stratikos, Efstratios
Abstract : Objectives: The efficacy of cancer immunotherapy, including treatment with immune-checkpoint inhibitors, is often limited by ineffective presentation of antigenic peptides that can elicit T-cell mediated anti-tumor cytotoxic responses. Therefore, manipulating antigen presentation is an emerging approach for enhancing the immunogenicity of tumors in immunotherapy settings. ER aminopeptidase 1 (ERAP1) is an intracellular enzyme that trims peptides that can bind onto MHC class I molecules (MHC-I). We hypothesized that pharmacologically inhibiting ERAP1 in cells can regulate the global cellular immunopeptidome. Methods: we treated the A375 melanoma cell line with a recently developed potent ERAP1 inhibitor and analyzed the presented MHC-I peptide repertoire by isolating MHC-I, eluting the bound peptides and identifying them using capillary chromatography and tandem mass spectrometry. Results: Although the inhibitor did not negatively affect overall MHC-I presence on the cell surface, it induced significant changes on the presented peptidomes, both at the qualitative and quantitative levels. Specifically, inhibitor treatment altered about half of the total 3204 identified peptides and about one third of the peptides predicted to be good ligands for MHC-I, affected length and sequence without however interfering with basic binding motifs. Surprisingly, the inhibitor enhanced predicted overall MHC-I binding affinity by reducing presentation of sub-optimal long peptides and generating many high-affinity 9-12mers suggesting that baseline ERAP1 activity in this cell line is destructive for many potential epitopes. Conclusions: Our results suggest that chemical inhibition of ERAP1 is a valid approach for manipulating the immunopeptidome of cancer with potential applications in standalone or combination immunotherapy.